Lipid-packing perturbation of model membranes by pH-responsive antimicrobial peptides - Alvares, Dayane S. [UNESP]; Viegas, Taisa Giordano [UNESP]; Ruggiero Neto, João [UNESP] (Springer Nature, 2017)
The indiscriminate use of conventional antibiotics is leading to an increase in the number of resistant bacterial strains, motivating the search for new compounds to overcome this challenging problem. Antimicrobial peptides, acting only in the lipid phase of membranes without requiring specific membrane receptors as do conventional antibiotics, have shown great potential as possible substituents of these drugs. These peptides are in general rich in basic and hydrophobic residues forming an amphipathic structure when in contact with membranes. The outer leaflet of the prokaryotic cell membrane is rich in anionic lipids, while the surface of the eukaryotic cell is zwitterionic. Due to their positive net charge, many of these peptides are selective to the prokaryotic membrane. Notwithstanding this preference for anionic membranes, some of them can also act on neutral ones, hampering their therapeutic use. In addition to the electrostatic interaction driving peptide adsorption by the membrane, the ability of the peptide to perturb lipid packing is of paramount importance in their capacity to induce cell lysis, which is strongly dependent on electrostatic and hydrophobic interactions. In the present research, we revised the adsorption of antimicrobial peptides by model membranes as well as the perturbation that they induce in lipid packing. In particular, we focused on some peptides that have simultaneously acidic and basic residues. The net charges of these peptides are modulated by pH changes and the lipid composition of model membranes. We discuss the experimental approaches used to explore these aspects of lipid membranes using lipid vesicles and lipid monolayer as model membranes.
Keywords: Antimicrobial peptides; GUVs; Lipid monolayers; Lipid-packing perturbation; Model membranes